2018
DOI: 10.2141/jpsa.0170185
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like Peptide-1 Receptor Expression in the Pancreatic D Cells of Three Avian Species; White Leghorn Chickens, Northern Bobwhites, and Common Ostriches

Abstract: Glucagon-like peptide (GLP)-1 is released from the intestinal L cells in response tofood ingestion and stimulates insulin secretion from the pancreatic B cells, by binding to its specific receptor (GLP-1R), which is expressed on the pancreatic B cells in the mammalian pancreas. Previously, we demonstrated that chicken GLP-1R was expressed on the pancreatic D cells by using a specific antibody against chicken GLP-1R. In the present study, we compared the localization of GLP-1R in the pancreases of three avian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…3) (Watanabe et al, 2014). Similar localization of cGLP1R has been observed in the pancreatic islets of other avian species, northern bobwhites, and common ostriches (Watanabe et al, 2018). Hall et al (1986) demonstrated a rapid increase in plasma glucose concentration after the intravenous injection of anti-somatostatin serum in domestic fowls.…”
Section: Glp-1 Secretion From Chicken L Cellssupporting
confidence: 66%
“…3) (Watanabe et al, 2014). Similar localization of cGLP1R has been observed in the pancreatic islets of other avian species, northern bobwhites, and common ostriches (Watanabe et al, 2018). Hall et al (1986) demonstrated a rapid increase in plasma glucose concentration after the intravenous injection of anti-somatostatin serum in domestic fowls.…”
Section: Glp-1 Secretion From Chicken L Cellssupporting
confidence: 66%
“…Glucagon-like peptide-1 in chickens is mainly released from the intestinal epithelial endocrine L cells (including the jejunum and ileum) stimulated by processing of proglucagon, protein, and amino acid [ 142 ]. The GLP-1 receptor (GLP-1R) also expresses in the brain and liver in chickens [ 143 ].…”
Section: Molecular Mechanism Of Osteocalcin In Flhs Chickensmentioning
confidence: 99%
“…In mammals, ucOCN also promotes insulin release mainly through two methods: one is directly affecting pancreatic β-cells, and another is indirectly simulating GLP-1 secretion from the small intestine and then GLP-1 activating pancreatic β-cells to secrete insulin [ 54 ]. However, unlike in mammals, the receptor of GLP-1 has been identified in chicken pancreatic D-cells secreting somatostatin rather than in pancreatic β-cells [ 142 , 144 ]. Overall, whether ucOCN affects GLP-1 in chickens is unclear.…”
Section: Molecular Mechanism Of Osteocalcin In Flhs Chickensmentioning
confidence: 99%